Virtual primary care for people living with dementia in Canada: cross-sectional surveys of patients, care partners, and family physicians - Vladimir Khanassov; Deniz Cetin-Sahin; Sid Feldman; Saskia Sivananthan; Allan Grill; Isabelle Vedel (BMC Primary Care)
Abstract Background Virtual care (VC) for dementia in primary care settings is an important aspect of healthcare delivery in Canada. However, the evidence informing optimal and sustainable provision of VC for persons living with dementia (PLWD) and their care partners is scarce. The objectives of this study were to (1) describe the frequency of VC use, (2) identify characteristics of PLWD, care partners, and family physicians (FPs) that are associated with the use of VC, and (3) explore FPs’ perceptions of barriers and facilitators to provide VC for PLWD and their care partners. Methods The Alzheimer Society of Canada and College of Family Physicians of Canada conducted three nationwide cross-sectional surveys between October 2020 and April 2021: (1) One with PLWD, (2) one with care partners of PLWD, and (3) one with FPs. Virtual care was defined as two-way synchronous communication by telephone and/or a web camera. The prevalence of VC use among FPs, PLWD, and care partners was described. Logistic regression models were used to determine characteristics of participants (sociodemographic, urbanicity, frequency and availability of support for connecting with FPs, and FPs’ practice characteristics) associated with any VC use (phone and/or video). Inductive thematic analysis of open-ended questions explored FPs’ perceptions. Results 131 PLWD, 341 care partners, and 125 FPs participated. 61.2% of PLWD, 59.5% of care partners, and 77.4% of FPs reported using VC. The models for PLWD (included age and ethnicity) and care partners (included gender/sex, urbanicity, and receiving support from a family member/friend to connect with FP) were inconclusive. FPs with > 20 years in practice were less likely to provide VC (OR = 0.23, 95%CI: 0.08–0.62, p < 0.01). FPs perceived that preferences regarding virtual vs. in-person care, office/family support, technology and family presence, and remuneration for FPs influenced VC use. Conclusions Virtual primary dementia care uptake in Canada is substantial and mainly performed via telephone. According to FPs, physician-patient-caregiver partnerships and infrastructure for VC play key roles in using VC. Virtual care could facilitate access to primary care and minimize potential disruptions to in-person care for PLWD. Outcomes of virtual primary care for dementia need further investigation.